2003
DOI: 10.1016/s0035-9203(03)90087-3
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis prophylaxis in vivo using N,N-Diethyl-m-toluamide (DEET)

Abstract: Topical N,N-Diethyl-m-toluamide (DEET) was studied as a schistosomiasis prophylactic in vivo for the use of individuals with limited exposure. Fifteen subjects, on a 3-week expedition to Lake Malawi in September 2001, applied 50% DEET to their skin after exposure to lake water. No subjects developed evidence of a new infection at 3-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The use of petroleum jelly and vigorous drying with towels, with application of ethanol to exposed skin, has been proposed as an effective means of reducing cercarial penetration, but no study has demonstrated the effectiveness of this procedure [25,61]. In contrast, the use of N , N ‐diethyl‐m‐toluamide 50% ointment in 15 travellers at Lake Malawi was associated with the absence of infection during a 3‐month follow‐up period [70]. Prior to being used for personal cleaning, contaminated water should be heated to 50°C for 5 min or treated with iodine or chlorine.…”
Section: Preventionmentioning
confidence: 99%
“…The use of petroleum jelly and vigorous drying with towels, with application of ethanol to exposed skin, has been proposed as an effective means of reducing cercarial penetration, but no study has demonstrated the effectiveness of this procedure [25,61]. In contrast, the use of N , N ‐diethyl‐m‐toluamide 50% ointment in 15 travellers at Lake Malawi was associated with the absence of infection during a 3‐month follow‐up period [70]. Prior to being used for personal cleaning, contaminated water should be heated to 50°C for 5 min or treated with iodine or chlorine.…”
Section: Preventionmentioning
confidence: 99%
“…Coeliac disease is a common condition (prevalence about 1:300 using serological tests) but frequently undiagnosed in adulthood, particularly when gastrointestinal symptoms are absent. 1,2 In this patient, severe malabsorption led to vitamin K deficiency, and the resulting anticoagulated state predisposed her to massive bilateral adrenal haemorrhage.…”
Section: Bilateral Massive Adrenal Haemorrhage Revealing Coeliac Diseasementioning
confidence: 90%
“…Prophylactic DEET has been shown to reduce the risk of acquiring schistosomiasis infection. 1 Schistosomiasis has three distinct clinical syndromes. 2 The first, 'swimmer's itch', occurs in response to cercarial penetration of the skin.…”
mentioning
confidence: 99%
“…Engineering projects and sanitation campaigns-that is to say, greater environmental management-helped make the tropics safer for foreigners, which led some to question theories of environmental determinism. 55 Of course, climatic determinism did not vanish altogether, as colonialist and racist notions of the "white man's burden" persisted at the turn of the twentieth century. 56 In the greater Caribbean region, diseases such as malaria and yellow fever had crippled U.S. troops in the Spanish-American War and workers building the Panama Canal.…”
Section: Medicinal Climatesmentioning
confidence: 99%